2007
DOI: 10.1068/d1103
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, Cultural Economy, and Not-So-Global Cities: The New Zealand Designer Fashion Industry

Abstract: IntroductionDespite the recent reinvigoration and high visibility of designer fashion in the world media, there is surprisingly little academic literature examining designer fashion and cities in the context of globalization. The broader literature on fashion and cities tends to focus on how fashion factors into themes of urban renewal (for example, Crewe and Beaverstock, 1998;Crewe and Lowe, 1996;Scott, 1995;1996) and/or of the historical development of fashion spaces and cosmopolitan identities in urban cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…Approximately one third (29%) of designers suggest that staying in Toronto often means giving up profits and committing oneself to a smaller business, but ultimately the connections they forge with local industry and with a customer base are worth it (interviews). These findings echo those of Larner et al (2007) who found that independent fashion designers from New Zealand typically do not aspire to leave the country or join international fashion houses abroad. Instead, their goal is to remain a niche player at the cutting edge of global fashion currents.…”
Section: Cultural Diversity Of Consumer Basesupporting
confidence: 88%
See 1 more Smart Citation
“…Approximately one third (29%) of designers suggest that staying in Toronto often means giving up profits and committing oneself to a smaller business, but ultimately the connections they forge with local industry and with a customer base are worth it (interviews). These findings echo those of Larner et al (2007) who found that independent fashion designers from New Zealand typically do not aspire to leave the country or join international fashion houses abroad. Instead, their goal is to remain a niche player at the cutting edge of global fashion currents.…”
Section: Cultural Diversity Of Consumer Basesupporting
confidence: 88%
“…But small enough to really take something and be able to make it popular without diluting it with all the others things that other people are trying to do" (interview, fashion designer, female, 14 August 2007). Our interviews suggest that it is easier to build and penetrate social networks with the media, with consumers, and with other designers in a 'not-so-global city' (see also Larner et al, 2007).…”
Section: Cultural Diversity Of Consumer Basementioning
confidence: 93%
“…The mid-1990s saw an opportunity for New Zealand designer fashion to develop for the first time, with local labels such as World and Zambesi appearing on the international stage, first at the Mercedes Benz Australian Fashion Week in 1997and 1998and then at London Fashion Week in 1999(Larner, Molloy and Goodrum 2007. In that time, the creative industries received a flood of government attention at a national level which has filtered through to local government.…”
Section: Introductionmentioning
confidence: 96%
“…The design of fashion in New Zealand has, for the most part, relied on following fashion trends from the major fashion cities of Paris and London and re-interpreting them for a local market (Larner, Molloy and Goodrum 2007). This practice has been both observed, in a rather naive manner, as the normal role of the 'industrial designer' (Schwimmer 1949) as well as criticized as an undesirable practice (Sterling 1991).…”
Section: Introductionmentioning
confidence: 98%
“…A probable exception is the case of New Zealand: this country is informative in the sense that it was in the forefront of neoliberal market reforms and the import of fresh policy agendas, although it is located geographically in the periphery (cf. Larner et al 2007;Prince 2010b). Eastern European cities were also studied marginally in this type of literature.…”
Section: Creative Capital Policy Mobilities and The Post-socialist Citymentioning
confidence: 99%